Self‐Assembly: Self‐Assembly of Microparticles by Supramolecular Homopolymerization of One Component DNA Molecule (Small 26/2019). Issue 26 (26th June 2019) - Zeng, Jie; Fu, Wenhao; Qi, Zhenping; Zhu, Qiushuang; He, Huawei; Huang, Chengzhi; Zuo, Hua; Mao, Chengde
Abstract : In article number1805552, Hua Zuo, Chengde Mao, and co‐workers describe an elegant method to assemble DNA microparticles (DNAµPs), relying on self‐assembly of multiple copies of the same, short, component DNA strand. The resulting DNAµPs can present single stranded DNA tails on their surfaces to stimulate innate immune responses and capture other single‐stranded nucleic acids.